Turkish Nationalism in 2025 in the Shadow of Islamism and Secularism - Fiere, Galu Putri; Surwandono, Surwandono (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2026)
This study discusses the dynamics of Turkish nationalism in 2025 which is characterized by a high inflation rate, but is not accompanied by a political crisis or national disintegration. This phenomenon is interesting because economic crises usually trigger social and political tensions, but in Turkey it is quite the opposite. The government is able to manage the political dynamics of Islamist and secular groups productively, making this division a social capital to strengthen national unity. This research uses a qualitative approach by observing social discourse, government policies, and community responses to national issues. The results show that Turkish nationalism is not uniform, but rather divided between those who support secularism as a national identity and those who see Islam as an important part of national identity. Despite the tensions between the two groups, they have in common in terms of commitment to the integrity and sovereignty of the country. The main difference lies in the way they interpret national identity.